Confirmatory factor Analysis of Thai Tourists in Decision Making for Cinema Film. - Poltanee , Issarapong; Boonphetkaew , Umaporn (Business Administration and Management Journal Review, 2023)
The aim of this research was to study the behavior of and the motivation of Thai tourists to visit the cinema and a corroborative analysis of the decision to visit the cinema The sample was 200 Thai tourists. Data were collected by questionnaires and data were analyzed by descriptive statistics and corroborative elements. The results show that most tourists visit first and get their information through social media. It usually takes place during the weekends to visit. Popular with private cars which looks like traveling with friends and has the most impression of watching the Sri Krung sound cinema In addition, the travel decision-making model to the cinema has an index Chi-Square = 34.97 p-value = 0.05 GFI = 0.96 NFI = 0.96 CFI = 0.98 RMSEA = 0.05 RMR = 0.01. The tourist film archives need to focus on the study of the tourism experience. image of tourist attractions overall satisfaction which will contribute to the intention of returning to travel.